The Effectiveness of Customer Satisfaction on Selected Fast-Food Chain Along Fairview, Quezon City: Basis for Recommendation: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to find out The Effectiveness of Customer Satisfaction onSelected Fast-Food chains along Fairview, Quezon City: Basis for Recommendation. Thisresearch aims to gain knowledge and awareness of the fast-food chain along FairviewQuezon City.The finding shows that customer satisfaction, customer service as well as the drive-thruservice got the highest composite mean out of the others, but between the drive-thru andcustomer service, customer service got the highest weighted mean of 3.42, which isinterpreted as Strongly Satisfied.The results show that most of the respondents are pleased with how the crew or staff treatedthem with kindness and friendliness; through the process of this paper, the researchers wereable to see the real problem that occurred in each of the respondents' situations. There is aneed for attention and awareness of the customer if they give better satisfaction to everyone.
Keywords: Hospitality Management